Analisis Strategi Pengembangan Komoditas Lokal Bawang Merah Topo (Allium cepa) Kelurahan Topo Kota Tidore Kepulauan Provinsi Maluku Utara - Mardiyani Sidayat; Sartika Syafi; Eka Kusuma Dewi; Mukhlis Mukhlis (Program Studi Agribisnis Fakultas Pertanian, 2026)
Topo red onions are a local horticulture commodity originating in North Maluku. This product is a native plant traditionally cultivated by the farmers in Topo village, Kota Tidore Regency. Analyzing local commodity development strategies is essensial to guide the regional government and other relevant stakeholders in formulating sustainable agricultural development programs. The objective of this research is to formulate a development strategy for Topo red onion to ensure their sustainability in the future. The development strategy for Topo red onion was determined using a SWOT analysis, aimed at identifying strategies that can be used to maintain the sustainability of this endemic crop and supporting livelihoods for the local community. The result indicated a total IFAS score of 3.64, consisting of a strength score of 3.04, with the highest strength score of 0.52, representing superior varieties, and a weakness score of 0.6, with the lowest weakness score of 0.04, representing small-scale holders, as both commodities are still cultivated. Meanwhile, the total EFAS value obtained for the development of Topo red onion commodity was 3.02, comprising an opportunity score of 2.24 with the highest opportunity score of 0.72, specifically related to market opportunities, and a threat score of 0.78 with the lowest threat factor score of 0.12, connected to a limited cultivation development program